Climate Change Impacts on Road Infrastructure Resilience in Bireuen Regency, Aceh: An Environment-Based Adaptation Approach - Basrizal; Cut Azizah; Rahmat Abbas (Yayasan Sagita Akademia Maju, 2026)
The escalating frequency and intensity of climate-induced extreme weather events present a critical challenge to the durability and functionality of road infrastructure, particularly in vulnerable tropical regions. This study provides a comprehensive analysis of the impacts of climate change on road infrastructure resilience in Bireuen Regency, Aceh, Indonesia. Employing a mixed-methods approach, the research integrates historical climate data (2015-2023) from the Meteorology, Climatology, and Geophysics Agency (BMKG), field survey data on road damage, and questionnaire responses from key stakeholders, including road users and local government officials. The findings reveal a statistically significant upward trend in extreme rainfall events, which correlates strongly with the prevalence of specific road damage modalities, predominantly potholes (45%) and crocodile cracking (30%). A thorough assessment of the road network condition indicates that only 51.19% is classified as being in good condition, with a substantial 42.46% suffering from light to severe damage, underscoring a high degree of climate vulnerability. The study concludes that a multifaceted adaptation strategy is imperative. Key recommendations include the urgent enhancement of drainage systems, the adoption of climate-resilient construction materials, the implementation of GIS-based hazard zoning, and the strict application of sustainable road management standards as outlined in national regulations. This research offers valuable evidence-based insights for policymakers and engineers aiming to bolster the climate resilience of critical infrastructure in disaster-prone areas.